Gut–Liver Axis: Liver Sinusoidal Endothelial Cells Function as the Hepatic Barrier in Colitis-Induced Liver Injury - Wang, Yang; Zhang, Yifan; Liu, Yun; Xu, Jun; Liu, Yulan (Frontiers in Cell and Developmental Biology, 2021)
Background Based on the gut–liver axis theory, a leaky gut can aggravate liver injury. However, clinical studies suggest that although gut mucosa damage is commonly observed in inflammatory bowel disease (IBD), it seldom leads to severe liver injury. We hypothesize that there is a hepatic barrier in the gut–liver axis, which protects the liver against gut-derived invasive factors. Methods Colitis was induced by dextran sulfate sodium (DSS) in eight different liver injury models in Sprague–Dawley rats. Liver sinusoidal endothelial cell (LSEC) injury was evaluated by a scanning and transmission electron microscope. Neutrophils were depleted by injection of anti-rat polymorphonuclear serum. Two pneumonia models were also induced to investigate the mechanism of neutrophil recruitment and activation. LSECs isolated from rat liver were used to investigate the effect on neutrophil recruitment and activation. Results Among eight liver injury models, DSS colitis had no effect on liver injury in three models with normal LSECs. In the other five models with LSEC rupture, liver injury was significantly exacerbated by colitis, and increased hepatic neutrophil accumulation was observed. When neutrophils were depleted, colitis-induced liver injury was significantly attenuated. In pneumonia, liver injury, and colitis models, the level of CXCL1 correlated with the recruitment of neutrophils in different tissues, while DSS colitis and LSEC injury synergistically contributed to increased CXCL1 expression in the liver. In colitis-induced liver injury, neutrophils were activated in the liver. Injured LSECs showed both structural and functional changes, with significantly increased expression of CXCL1 and TNF-α under the stimulation of lipopolysaccharide (LPS). The combination of gut-derived LPS and LSEC-derived TNF-α led to the activation of neutrophils, characterized by enhanced production of reactive oxygen species, pro-inflammatory cytokines, and the formation of neutrophil extracellular traps. Conclusion LSECs constitute a vitally important barrier in the gut–liver axis, defending the liver against colitis-induced injury. When LSECs are damaged, they can turn into a pro-inflammatory pattern under the stimulation of LPS. LSEC injury and colitis-derived LPS synergistically contribute to the recruitment and activation of hepatic neutrophils. Neutrophils play a pivotal role as a downstream effector in colitis-induced liver injury.